Megjegyzések navratil ákos elmélettörténetéhez - Katalin Csató (Hungarian Academy of Sciences, Institute of Economics, 2008)
Ákos Navratil (1875-1952) is an outstanding theoretical economist from the first half of the 20th century. A selection of his works was published as volume 8 in the series Classics in Hungarian Economics (Old truths and new theories in economics by Ákos Navratil, (int., ed. by M. Hild)). The study focuses on one element from his wide array of interests in economic theory: his evaluation of the physiocracy. The main topics addressed include a historical evaluation of the physiocrats in terms of their relationship to Adam Smith, the connection of their views to (contemporary) philosophy, and the change in judgment of them in the last third of the 18th century. The study's approach results in a slightly different view than that expressed by Navratil.
Keywords: 330; Ákos Navratil; Physiocracy; Adam Smith; Philosophy; History of Economic Thought; Wirtschaftswissenschaft; Ökonomische Ideengeschichte; Physiokratie; Ökonomen; Ungarn